Reduce of Poverty Indonesia for Best Effect of MSMEs - Diwayana Putri Nasution (Britain International for Academic Research (BIAR) Publisher, 2023)
The purpose of this study is to analyze the existence of MSMEs in reducing poverty in Indonesia. Where there are two dependent variables, namely GDP and Poverty and there are five independent variables, namely the number of MSMEs, investment, population, unemployment, and exports. This study uses secondary data or time series, namely data from 2004 to 2018. The data analysis model in this study uses the 2SLS Simultaneous Regression method. There is one variable for simultaneous results that shows an effect on GDP, namely investment has a positive and significant effect on poverty. For the effect on poverty, there is one variable for simultaneous results which shows the effect on poverty, namely unemployment has a positive and significant effect on poverty.